Keterlibatan Ayah dalam Pengasuhan Pada Remaja - Riau Roslita; Agnita Utami; Ika Permanasari (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
The involvement of fathers in adolescents in parenting is an effort of how much fathers are involved in activities, direct contact and provide support to adolescents. Support from family is very important in parenting, especially fathers. This study aims to describe the involvement of fathers in the care of adolescents. This type of research is quantitative with a simple descriptive design. The number of samples in this study were 110 teenagers in the Bukit Raya District, Pekanbaru City. Sampling in this study is using the snowball sampling method. Retrieval of data using a questionnaire. The analysis of this research used univariate with the presentation of frequency distribution and percentage. The results of this study found that the involvement of the father in the high category was 98 people (90%). Nurses play an important role in providing health education to parents about the importance of fathers' involvement in the care of adolescents. Keywords: Father Involvement in Parenting, Adolescents